Screening and Isolation of Extracellular Protease Producing Bacteria from the Maharloo Salt Lake: Extracellular protease producing bacteria - Younes Ghasemi; Sara Rasoul-Amini; Alireza Ebrahiminezhad; Aboozar Kazemi; Maryam Shahbazi; Najme Talebnia (Iranian Journal of Pharmaceutical Sciences, 2011)
Screening and identification of moderately halophilic protease producing bacteria from different regions of Maharloo, a hypersaline lake in the southern area of Iran, were the objectives of this study. In the preliminary screening, 16 isolates exhibited proteolytic activity on saline skim milk agar. All isolates were able to grow comfortably in the media containing 7-15% of salt. Protease activity was assessed through in vitro colorimetric assays for general proteases and the strains were identified by 16S rDNA molecular marker. In comparison to Gram-negative bacteria, the Gram-positive rods, displayed higher proteolytic activities, and Bacillus sp. BCCS 041 was found as the highest protease producing strain with 0.43 U/ml of supernatant activity.